Involving peers in research: the UNSW community reference panel - Melinda Walker; Kim Beadman; Steve Griffin; Mitchell Beadman; Carla Treloar (BMC, 2019)
Abstract There is limited literature about how to best "do" community involvement in research and no one model of community involvement in research that has been shown to be more effective than others. This paper presents one way to receive the input of people with experiences relevant to research with marginalised groups, including people who use and inject drugs. The UNSW Community Reference Panel is a virtual network of people from across Australia who are engaged to provide input and consultation on research design, processes, materials, and outputs. Although this panel goes some way towards community involvement and consultation in the research process, it does not take the place of other aspects of community governance and ownership, especially as informed by principles of research with Indigenous peoples. This model is an example of a means to bring the voices and perspectives of people who are generally excluded from the research and decision-making structures that affect their lives, including people who inject drugs, to influence the questions that are asked in research, how research gets done, and to what purpose research findings are put.